Quality performance of Universiti Teknologi MARA Sarawak 2003 / Iris Syawe Seh Ling … [et.al.] - Seh Ling, Iris Syawe; Nee' Gaik, Mary Gunjew; Ching, Goy Siew; Abdillah, Azlin; Chiok Choo, Dorothy Kueh; Jaya, Serah; Lee Hun Leong, Nagarajah; Goh, Kelvin Tee Hiong (2004)
This study was conducted to monitor the quality performance of Universiti Teknologi MARA (UiTM) Sarawak based on the recommendations of the 2002 study by determining the quality measurement index on the standard of services rendered to staff and students, and the ROKUM Quality Index (RQI). The first part of the study was undertaken by conducting questionnaire surveys on students and staff. The questionnaires for students and staff used in the 2002 study were redesigned to overcome the limitations of that study. A total of 1,658 students and 204 staff responded. In the second part of the study, the RQI Instrument for self-evaluation based on the eight criteria laid out in the ROKUM was refined and up-dated to incorporate as much as possible the items in the Malcolm Baldrige “2003 Education Criteria For Performance Excellence” model.